Students' Perceptions of the Prohibition of Smoking in Public Middle Schools - Indah Zhafirah, Annisa; Ridwan, M; Rahayu Ningsih, Vinna; Novita Eka Rini, Willia; Sari, Puspita (Rifa'Institute, 2023)
Introduction: The smoking ban policy in Indonesia has not been fully complied with by the community, one of which is the policy of prohibiting smoking in schools. Smoking behavior at school is influenced by several factors such as knowledge, environmental influences, experience, and perception. One factor in the lack of compliance with the no-smoking policy in schools is the perception of a smoking ban. Objective: This study aims to determine students' perceptions regarding smoking bans in the school environment. Method: This research uses qualitative research methods with a case study approach. Result and Discussion: In terms of information, it has run optimally. In terms of social rules, the school has implemented the rules firmly, but it is not optimal enough because there are still students who do not obey. In terms of experience, students only know about the smoking ban in the school environment when they first enter JHS, have curiosity and pleasure when consuming cigarettes. The environment of students shows that parents and friends of students are very influential. Conclusion: Students' perceptions of smoking bans are influenced by parental factors that often smoke in front of children, and peers who become friends of students to smoke together. This makes students less compliant with the policies that have been implemented by the school